Chapter 35 Discovery and Inquiry Pathways to Navigating the Routledge International Handbook of Failure - Fraser, Gertrude Jacinta (Taylor & Francis, 2023)
Our aim in this afterword is to take the position of an informed reader in the social sciences who seeks as we did to discover points of entry into critical failure studies as developed within the Routledge International Handbook of Failure. Because the book ranges across disciplines and subject matter, we find that the introduction provides an ample overview of the chapters and the goals of the work. We have chosen to ask the question: how might a reader navigate this volume and approach its many theories, definitions, and perspectives? To accomplish this, we offer a brief view of two current projects, distinct in their foci, which served as points of entry to this body of work. First, a project on failure narratives among women in the academy, and second, a project which revolves around the coronavirus pandemic and vaccine hesitancy across six nations. In so doing, we hope to show how particular chapters provide surprises, insights, and theoretical frameworks that inform and deepen our understanding of this nascent and rich inquiry into the nature of failure and how it is problematized and challenged.